Effect of NPK Fertilizer and Vermicompost on The Vegetative Growth of Green Eggplant (Solanum melongena L.) - Putra, Masaradi; Raksun, Ahmad; Sedijani, Prapti (Jurnal Biologi Tropis, 2025)
Plant growth and development require nutrients, which can be provided through fertilization in the form of both inorganic and organic fertilizers. This study aims to determine the effect of NPK fertilizer, vermicompost, and the combination between the two on the vegetative growth of green eggplant. In this study, a two-factor Complete Random Design was used consisting of NPK fertilizer and vermicompost treatment with each using 5 treatment levels and carried out with 4 replicates. The parameters measured were stem height, number of leaves, leaf area, plant dry weight and plant wet weight. The data obtained was analyzed by the Anova two-way and continued with the DMRT. The results showed that the application of NPK fertilizer had a significant effect on all observed growth parameters. The application of vermicompost had a significant effect on all observed growth parameters. The application of a combination of NPK fertilizer and vermicompost had a significant effect on several growth parameters, including plant height, leaf area, dry weight  and wet weight of the plant, but  did not have a significant on the number of leaves.